Right brain management: need of the hour - Saran, Prem (2000)
Human Resource Development has become the key functional area in Public Administration, and in Management generally, since technology per se no longer grants sufficient competitive advantage in today's global world of accelerated dissemination of information and knowledge. People resources are, therefore, to be optimally tapped for organisational excellence, and here again the over-emphasised leftbrain skills of analysis and logical manipulation are being found to be insufficient to meet the transformational needs generated by quickening change. Again, recent studies have shown that the need of the hour is "rightbrain management". And it is here that Indic knowledge systems find their entry into contemporarymanagement theory and practice. The author accordingly outlines a traditional Indian technique of disciplined rightbrain-tappling, suitably modified for a contemporary audience. Thereby individual creativity can be systematically released, to generate organisational synergy. The author sums up with a brief survey of current research in the Behavioural Sciences, such as Maslow's work on "self-actualisation", Cziksentmihalyi's on "flow", and Seligman's on "learned optimism". He then concludes with a reference to Debashis Chatterjee's concept of "leading consciously", which has recently been highlited by the Harvard Business School, and which is related to the ultimate Maslewian human need for "transcendence ". - Reproduced
Keywords: Human resources development